Green Bonds: A Catalyst for Sustainable Development - Aggarwal, Dr. Shalini; Pathak, Ms. Shipra (The journal of contemporary issues in business and government, 2021)
There is a need to cut down CO2 emissions by at least 45% by the year 2030 to attain a net zero. There is a need around the globe for a wide ranging shift to a low carbon foot print economy with a view to restrict the rising earth temperature status within 1.5 to 2 degrees. To achieve this objective one needs to support technological shifts and advances as well implementation of government policies on climate controls in the form of carbon taxes, green growth policies. Green bonds are instruments aimed at encouraging sustainability and to help build up on projects focused at environmental protection and implementing other climate related projects. The paper aims at studying comprehensively the global operation of green bond markets and its ongoing development. The result predicts that there is positive impact of these projects on the sustainable development. Use of Renewable Capacity From Solar, Wind And Hydro Technologies has been used that decreases Co2 Emission and thus significantly impacting the environment.